2018
DOI: 10.1037/emo0000348
|View full text |Cite
|
Sign up to set email alerts
|

Valuing calm enhances enjoyment of calming (vs. exciting) amusement park rides and exercise.

Abstract: Do people derive more enjoyment from activities that match how they ideally want to feel (their "ideal affect")? Affect valuation theory (AVT) predicts that they do; however, no study has directly examined whether this is the case. Therefore, the authors conducted 4 studies that examined whether valuing calm and other low arousal positive states (LAP) increased enjoyment of calming (vs. exciting) activities. In Study 1, the more participants valued LAP, the more enjoyment they recalled during calming (vs. exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
1
20
2
Order By: Relevance
“…Indeed, this may explain why people seek activities and objects that match their ideal affect. Consistent with this idea, using both correlational and experimental approaches, we found that across cultures, the more people value LAP, the more they actually enjoy calming (vs. exciting) activities such as low (vs. high) intensity exercise and calming (vs. exciting) amusement park rides (e.g., sky lift vs. free fall) in the moment, even after controlling for their global actual LAP [27]. …”
Section: Links Between Ideal Affect and Momentary Actual Affective Exmentioning
confidence: 75%
“…Indeed, this may explain why people seek activities and objects that match their ideal affect. Consistent with this idea, using both correlational and experimental approaches, we found that across cultures, the more people value LAP, the more they actually enjoy calming (vs. exciting) activities such as low (vs. high) intensity exercise and calming (vs. exciting) amusement park rides (e.g., sky lift vs. free fall) in the moment, even after controlling for their global actual LAP [27]. …”
Section: Links Between Ideal Affect and Momentary Actual Affective Exmentioning
confidence: 75%
“…Previous research suggests if activities or others’ facial expressions match people’s own ideal affect (“ideal affect match”; Chim et al, 2018), people respond more positively. For example, the more people ideally wanted to feel calm, the more they enjoyed calming versus exciting rides in amusement parks (Chim et al, 2018). These findings suggest an ideal affect match influences judgments as people derive more enjoyment from activities that match their ideal affect.…”
Section: Previous Researchmentioning
confidence: 99%
“…Idealized affect in turn predicts typically experienced affect ostensibly because the experiences one might choose to engage in could differ by how one would like to feel during the experience. These experience selections are reflected in the products ( Chim et al, 2018 ; Park et al, 2020 ), professional services such as doctors ( Sims et al, 2018 ), and leaders ( Tsai et al, 2016 ) that are preferred cross-culturally. Higher arousal versions are preferred in Western cultures and lower arousal versions preferred in Eastern cultures.…”
Section: Introductionmentioning
confidence: 99%